Successful Fecal Microbiota Transplantation in a Patient Suffering From Irritable Bowel Syndrome and Recurrent Urinary Tract Infections. (14th October 2019) - Hocquart, Marie; Pham, Thao; Kuete, Edmond; Tomei, Enora; Lagier, Jean Christophe; Raoult, Didier
Abstract: Background: Irritable bowel syndrome (IBS) is a chronic and debilitating functional gastrointestinal disorder affecting 9%–23% of the population across the world. The relative efficacy of fecal microbiota transplantation (FMT) on IBS symptoms was demonstrated in a double-blind, randomized study. Methods: We describe the case of a 73-year-old woman suffering from IBS (abdominal pain, bloating, and abundant and disabling diarrhea, with 10–15 stools a day) and repetitive urinary tract infection (UTI; 5 episodes in 6 months, including 3 the last 2 months) for several years, generating an impaired quality of life. She received an FMT with 400 mL of fecal infusion from a healthy donor via a nasogastric tube after bowel lavage. Her digestive microbiota was analyzed using culturomic and metagenomic targeting 16S rRNA sequencing methods. Results: Eight months after transplantation, we observed a significant reduction in frequency and improvement in stool consistency (3–4 molded stools a day against 10–15 before the transplant) and no recurrence of urinary infection (as previously reported). Using culturomics, we found 12 bacteria present in the fecal infusion and post-transplant stool; these were absent pretransplant. Three of them ( Intestinimonas massiliensis, Oscillibacter massiliensis, and Provencibacter massiliensis ) were previously discovered and cultivated in our laboratory using culturomics. Using metagenomics, we also observed 12 bacteria, different from those observed during culture, that could have been transferred to the patient by FMT. Conclusions: In this case report, IBS symptoms and UTI frequency decreased after FMT UTI. Further studies involving more patients would be relevant to confirm this work and develop bacteriotherapy.